Analisis Perkembangan Komunikasi Massa Terhadap Pola Pikir dan Perilaku Masyarakat Di Era Society 5.0 - Khairul Rizki; Muhammad Eka Answaril Ikhsan (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the influence of mass communication developments on people's mindsets and behavior in the context of social change in the Society 5.0 era. In an increasingly digitalized society, mass communication is no longer one-way, but interactive and real-time, influencing how people understand, respond, and behave towards social reality. The approach used in this study is descriptive qualitative with data collection methods in the form of in-depth interviews, observations, and documentation studies. Ten forms of significant influence of mass communication on social behavior were also found, ranging from changes in consumption patterns to the formation of digital solidarity. Therefore, media literacy is very important so that people can respond to information wisely and build healthy social behavior. This study concludes that mass communication is one of the main forces that shape the dynamics of contemporary society in the Society 5.0 era.